Neurodidactics in Arabic Language Learning as a Foreign Language: The Integration of Arabic Linguistics and Cognitive Neuroscience - Muhammad Khoirul Umam (Lembaga Pengembangan Penelitian, Pengabdian, dan Publikasi, 2026)
This study aims to examine the role of neurodidactics in Arabic language learning as a foreign language through the integration of Arabic linguistics and cognitive neuroscience. This study employs a qualitative research method using a systematic literature review approach of relevant scholarly works in the fields of cognitive neuroscience, Arabic linguistics, and foreign language pedagogy. The analysis is conducted by examining the relationship between learners’ neurological processes—such as attention, memory, emotion, and brain plasticity—and effective strategies for learning Arabic. The discussion highlights how neurodidactic principles can be implemented in the teaching of phonological, morphological, syntactic, and semantic aspects of the Arabic language in order to enhance learners’ comprehension and retention. The findings indicate that the application of a neurodidactic approach can create learning environments that are more adaptive to the way the brain functions, increase learning motivation, and optimize cognitive processes in the acquisition of Arabic as a foreign language. In conclusion, the integration of Arabic linguistics and cognitive neuroscience through a neurodidactic approach provides a strong theoretical and practical foundation for the development of more effective, innovative, and scientifically grounded models of Arabic language learning.